If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3s + 20) = 80 Reorder the terms: 4(20 + 3s) = 80 (20 * 4 + 3s * 4) = 80 (80 + 12s) = 80 Add '-80' to each side of the equation. 80 + -80 + 12s = 80 + -80 Combine like terms: 80 + -80 = 0 0 + 12s = 80 + -80 12s = 80 + -80 Combine like terms: 80 + -80 = 0 12s = 0 Solving 12s = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Divide each side by '12'. s = 0 Simplifying s = 0
| y=ln(1.07) | | 500x+24=60 | | -5+10y=x | | X^2+6x-90=8 | | 2log(2x)=7 | | 2=-18+4x | | Logx+2=4 | | x(x^2+16+64)=9(x+8) | | 0.25x+1.5=7.5 | | 3x^4-8=56 | | 6p^2-11=0 | | 26/30x24000 | | -6(5-2x)=q | | 4/10-x)=25-x | | 2P^2-20P+32=0 | | x^(5/4) | | 3y+7x=42 | | x^5/4 | | 10=3r+7r | | X+240y=186 | | 3a-1.2=4 | | 4x+160y=224 | | X+3(x-1)=8-4(2x+3) | | 4(10-x)=25-x | | 25k^2+40k-20=0 | | A=90(n-5) | | 2(3a-1)=2(a+1) | | X+240y=106 | | 3(f+9)=30 | | 2x+14=34-8x | | 10=3(4x-3)-5 | | 6+3x=6+5x |